2014
DOI: 10.4322/rca.ao0921
|View full text |Cite
|
Sign up to set email alerts
|

Perfil sérico de alguns constituintes sanguíneos de ovelhas da raça Dorper no período gestacional e pós-parto

Abstract: RESUMO: Mediante a inexistência de estudos do perfil bioquímico de ovelhas da raça Dorper, objetivou-se avaliar alguns parâmetros sanguíneos em 20 ovelhas nos períodos pré-parto, parto e pós-parto. As ovelhas eram criadas em sistema semiextensivo. A partir do 90 dias de gestação, iniciou-se coleta de material biológico para análises laboratoriais, que foram efetivadas em diferentes tempos: -60, -30, -21, -15, -7 antes do parto; no momento do parto; 7, 14 e 28 dias pós-parto. Amostras de sangue foram coletadas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 8 publications
4
7
1
1
Order By: Relevance
“…The decrease in the concentrations of fructosamine during the prepartum period, continuing with decreases up to 15 days postpartum are coincident with the data observed by SANTOS et al (2014), in Morada Nova sheep, and contrary to those observed by SOARES et al (2014), who found no variation in the dynamics of fructosamine in Dorper sheep, during the same periods. Fructosamine is a blood biochemical variable that has not previously been used in metabolic energetic profile studies in Moxotó goats during gestation, delivery, and postpartum periods, being pioneered in this study.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The decrease in the concentrations of fructosamine during the prepartum period, continuing with decreases up to 15 days postpartum are coincident with the data observed by SANTOS et al (2014), in Morada Nova sheep, and contrary to those observed by SOARES et al (2014), who found no variation in the dynamics of fructosamine in Dorper sheep, during the same periods. Fructosamine is a blood biochemical variable that has not previously been used in metabolic energetic profile studies in Moxotó goats during gestation, delivery, and postpartum periods, being pioneered in this study.…”
Section: Discussionsupporting
confidence: 89%
“…The profiles represented by the cholesterol and triglyceride concentrations were within the normal range at different collection moments and without a regression effect in function of the days of the prepartum period. These data are discordant with those observed by SANTOS et al (2014) andSOARES et al (2014), who observed a decrease in the mean values of cholesterol and triglycerides until delivery and this continued to decrease in the postpartum period. GONZÁLEZ et al (2000) and GONZÁLEZ e SILVA (2003) state that their plasma levels are adequate indicators of total plasma lipids.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations